PEMBERDAYAAN PEKERJA MIGRAN: SUATU KONSEPSI MENGHAPUS MASALAH KESEJAHTERAAN SOSIAL DI KELURAHAN PRAWIRODIRJAN (Empowering of Migrant Workers: A Conception for Eliminating Social Welfare Problems in Prawirodirjan) - Nina Karinina (Politeknik Kesejahteraan Sosial, 2005)
Actually, a serious program for poverty alleviation has been started since the last five years. Ta alleviate poverty problem especially in urban areas should not be focused on physical infrastructure development alone. it should be considering the dimension of social development to make urban development to be more harmony. Poverty alleviation is almost considered as the ultimate goals of the city planning, and this problem caused by the process of urbanization.Contemporary social problems in urban areas such as financial assistant for the poor, adolescent problem, drug abuse, criminality, prosti tution, social dysfunction, social cinflict, etc. Efforts to prevent these problems are needed; and improvement the quality of life of migrant workers should be the priority for the government of the municipalities. Regarding these problems, results of the the research in Keluraban Prawirodirjan found evidences that the empowerement program directed to migrant workers resulting a good lessons lerned for us.